Research on the Construction Method of Real-time Scheduling Process and Bus Scheduling Table based on WorldFIP Fieldbus - Liu, Yuliang; Rao, Ziyi; Zhe, Qiang; Sun, Hongxiao; Liang, Geng (International Journal of Mechanical and Electrical Engineering, 2024)
The WorldFIP protocol is the third part of the European standard EN-50150. It is particularly suitable for use in distributed computer control systems. WorldFIP provides data transfer services for variable exchange, and in order to cope with the real-time requirements of the system during variable transfer, the WorldFIP protocol provides communication services based on periodic and non-periodic identification exchanges, in which periodic exchanges have the highest priority and are scheduled cyclically according to the bus scheduling table at runtime. execution at runtime according to the bus scheduling table. Therefore, when constructing the scheduling table, the respective schedulability can be determined at pre-run time. For acyclic variable exchanges, the situation is different as they have a lower priority level and perform variable exchanges according to a first-come-first-served strategy. In this paper, from the perspective of variable exchange, we study the communication mode of the WorldFIP protocol, the process of cyclic and acyclic variable exchange, introduce a method for constructing bus scheduling tables based on microcycles and macrocycles, and finally give specific examples to prove the rationality of this method.